2000
DOI: 10.1093/qjmed/93.12.813
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and maternal outcomes in Indo-Asian compared to Caucasian women with diabetes in pregnancy

Abstract: Maternal and fetal complications are increased when pregnancy is complicated by diabetes, and this may be further influenced by racial and cultural differences. We examined fetal and maternal outcomes in Indo-Asian and Caucasian women attending the same antenatal diabetes service to see if there were any differences. Women with diabetes mellitus (type 1, type 2 and gestationally-acquired disease) complicating pregnancy, registered at the combined diabetes/antenatal clinic of this University teaching hospital o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…However, compared with our well-characterized population of pregnant women with type 1 diabetes, women with type 2 diabetes had comparable or better glycemic metabolic control but nevertheless a poorer pregnancy outcome. A few other studies find tendencies toward higher HbA 1c and fructosamine, among women with type 1 diabetes compared with women with type 2 diabetes, but only in the first part of pregnancy (4,6,19). This indicates that factors in addition to glycemic control are related to the poor outcome of pregnancies complicated by type 2 diabetes.…”
Section: Outcome Of Pregnancies In Women With Type 2 Diabetes During mentioning
confidence: 94%
See 3 more Smart Citations
“…However, compared with our well-characterized population of pregnant women with type 1 diabetes, women with type 2 diabetes had comparable or better glycemic metabolic control but nevertheless a poorer pregnancy outcome. A few other studies find tendencies toward higher HbA 1c and fructosamine, among women with type 1 diabetes compared with women with type 2 diabetes, but only in the first part of pregnancy (4,6,19). This indicates that factors in addition to glycemic control are related to the poor outcome of pregnancies complicated by type 2 diabetes.…”
Section: Outcome Of Pregnancies In Women With Type 2 Diabetes During mentioning
confidence: 94%
“…In addition, the study indicated that the outcome was poorer if type 2 diabetes was diagnosed during pregnancy compared with before pregnancy (6). The prevalence of type 2 diabetes in pregnancy was the highest in non-Caucasian women, who had a nonsignificantly higher HbA 1c during pregnancy (3,4,6).…”
Section: Diabetes Care 28:323-328 2005mentioning
confidence: 97%
See 2 more Smart Citations
“…12 Some data specific to women with GDM have suggested that adverse outcome risk may also vary by race/ethnicity. [13][14][15] Findings conflict, however, and recent data suggest the magnitude of racial/ethnic differences is small, particularly when individual, more narrowly defined racial/ethnic groups are evaluated. 16,17 The association of race/ethnicity with complications of GDM and the role GDM treatment may play thus remain unclear.…”
Section: Introductionmentioning
confidence: 98%